Modulation of autonomic activity in neurological conditions: Epilepsy and Tourette Syndrome - Nagai, Yoko (Frontiers in Neuroscience, 2015)
This manuscript considers the central but neglected role of the autonomic nervous system in the expression and control of seizures in epilepsy (small) and tics in Tourette Syndrome (TS). In epilepsy, consideration of autonomic involvement is typically confined to differential diagnoses (e.g., syncope), or in relation to Sudden Unexpected Death in Epilepsy (SUDEP). Investigation is more limited in Tourette Syndrome. The role of the autonomic nervous system in the generation and prevention of epileptic seizures is largely overlooked. Emotional stimuli such as anxiety and stress are potent causes of seizures and tic activity in epilepsy and TS, respectively. This manuscript will describe a possible neural mechanism by which afferent autonomic projections linked to cognition and behavior influence central thalamo-cortical regulation, which appears to be an important means for controlling both seizure and tic activity. It also summarizes the link between the integrity of the default mode network and autonomic regulation in patients with epilepsy as well as the link between impaired motor control and autonomic regulation in patients with TS. Two neurological conditions; epilepsy and TS were chosen, as seizures and tics represent parameters that can be easily measured to investigate influences of autonomic functions. The EDA biofeedback approach is anticipated to gain a strong position within the next generation of treatment for epilepsy, as a non-invasive technique with minimal side effects. This approach also takes advantage of the current practical opportunity to utilize growing digital health technology.